Tiempo y singularización. Enfoques de las dinámicas relacionales del Dasein en elaboraciones de Heidegger entre 1927-1930 - Butierrez, Luis (Pontificia Universidad Católica del Perú. Fondo Editorial, 2021)
En el siguiente trabajo nos detendremos en un análisis y reconstrucción de las relaciones entre singularización y tiempo, respecto de sus especificaciones en torno al instante, a partir de una relación entre las elaboraciones de Heidegger en Sein und Zeit y su curso de 1929-1930. En ese marco, nos proponemos demostrar que sus consideraciones en torno a la relación dinámica Dasein-temporalidad-singularización profundizan la comprensión de fondo en la que se articulan, a partir de un cambio de acento que permite precisar con mayor claridad el concepto relacional de Dasein frente a las perspectivas subjetivistas tradicionales. De esta manera, buscamos desarrollar las relaciones entre singularización-tiempo en la obra de Heidegger y cotejar desde allí las condiciones para un marco interpretativo y recepción acorde al marco comprensivo de su obra.

“Time and singularization. Approaches to the relational dynamics of Dasein in Heidegger’s elaborations between 1927-1930”. In the following work we will pause in an analysis and reconstruction of the relations between singularization and time, with respect to their specifications around the moment, from a relation between Heidegger’s elaborations in Sein und Zeit and his course from 1929-1930. In this framework, we intend to show that his considerations around the dynamic relationship Dasein-temporality-singularization deepen background understanding in which they are articulated, based on a change of accent that allows the relational concept of Dasein to be specified more clearly, versus traditional subjectivist perspectives. In this way, we seek to develop the relationships between singularization-time in Heidegger’s work and to compare the conditions for an interpretative and reception framework from there according to the comprehensive framework of his work.
Time and singularization. Approaches to the relational dynamics of Dasein in Heidegger’s elaborations between 1927-1930
Keywords: Mismidad; Instante; Temporalidad; Comprensión; Acontecimiento; https://purl.org/pe-repo/ocde/ford#6.03.01